Improving critical thinking skills and scientific attitudes by using comic - Putri, Mufida Awalia; Prodjosantoso, Anti Kolonial (Psychology, Evaluation, and Technology in Educational Research, 2020)
The objective of the study is to identify the fitness and the effectiveness of the comic that has been developed using Guided Inquiry Technique in improving the studentsâ€™ critical thinking skills and scientific attitudes for the learning process of Natural Science. The study itself is a research and development initiative that has adapted the model proposed by Borg & Gall. Within the conduct of the study, the limited experiment by means of one-group pre-test and post-test design had been conducted. On the other hand, within the conduct of the operational test, the quasi-experiment design in the form of non-equivalent pre-test post-test control group design had been adopted. The results of the study, thus, show that: (1) the Natural Science comic media has been fit for implementation with the â€œVery Goodâ€ category; and (2) the Natural Science comic media has been active in significantly improving the studentsâ€™ critical thinking skills. The mean score for the critical thinking skills of the students in the control group is 0.74 with the â€œHighâ€ category. In contrast, the mean score for the critical thinking skills of the students in the experimental group is 0.87 with the â€œHighâ€ category. In the same time, it is apparent that the improvement of the scientific attitude between the students in the control group and the students in the experimental group has been significant.